Dampak Sistem Informasi Manajemen Pendidikan (EMIS) terhadap Manajemen Sekolah yang Efektif di Tanzania - Julius Jonas Mbawala; Slamet Lestari; Ambakisye Mwakalindile (Postgraduate, University of Mataram, 2024)
The rapid advancement of science and technology has ushered in transformative changes in education management, embracing innovative tools and methods for more efficient and effective educational processes. The purpose of this study was to investigate the use of EMIS in enhancing effective school management and explore the challenges associated with it. The data were collected through semi-structured interviews with five principals of selected secondary schools found in Dodoma City, Tanzania. Qualitative data analysis techniques were used to analyze data with an audit trail and member checks to ensure the quality of the collected data. The research results show that EMIS plays a crucial role in efficiently managing schools. Principals rely on EMIS as a dependable repository for school data, for tracking attendance of both teachers and students, managing student enrollments, ensuring the efficient operation of school finances, enhancing communication, and improving the management of academic activities. However, challenges such as a shortage of ICT experts, inadequate internet connectivity, limited budgets, frequent electricity outages, the absence of user-friendly software, and difficulties in system integration and interoperability have been identified as hindrances to the effective utilization of EMIS in school management